Food and Feeding Habits of Citharinus citharus from Upper River Benue Yola, Adamawa State (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research determined the feeding intensity and stomach fullness of Moonfish (Citharinus citharus) of Upper River Benue. Sampling was done twice a month for the period of 3 months. The gut contents were analyzed using frequency of occurrence and numerical methods. The feeding intensity of the fish was determined visually after dissection and categorized. A total of 39 fish; 33 (84.6%) males and 6 (15.4%) females were sampled during the study. Food was not present in all guts of C. citharus. The present study showed that 39.4% of the male species had no food in their stomach, whereas 50% of the female species had empty stomach. It was observed that 18.2% and 16.7% of male and female had full stomachs respectively. This was followed by those with ¾full stomachs with percentage fullness of 15.2 % for male and 33.3% for female. Furthermore, 9.0% (male) and 0% (female) was recorded for ½full and ¼full 18.2% for male and 0% female stomachs respectively. Twelve (12) major items were eaten as food by C. citharus. These ranged from plant to animal materials. C. citharus fed on insect’s parts, fish parts, zooplanktons, phytoplanktons, sand, red worms, mud, roots, diatom and unidentified materials. In conclusion, C. citharus from Upper River Benue, Adamawa state fed on wide range of food items from plant to animal materials and can therefore be said to be omnivorous.